2019
DOI: 10.1038/s41598-019-54622-z
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa uses multiple receptors for adherence to laminin during infection of the respiratory tract and skin wounds

Abstract: Pseudomonas aeruginosa efficiently adheres to human tissues, including the lungs and skin, causing infections that are difficult to treat. Laminin is a main component of the extracellular matrix, and in this study we defined bacterial laminin receptors on P. aeruginosa. Persistent clinical P. aeruginosa isolates from patients with cystic fibrosis, wounds or catheter-related urinary tract infections bound more laminin compared to blood isolates. Laminin receptors in the outer membrane were revealed by 2D-immunb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The 6 × His-tagged proteins were expressed in E. coli BL21(DE3) (Novagen) after induction with 1 mM IPTG. Expressed proteins were purified on Ni-NTA resin columns (GE Healthcare, Chicago, IL) as previously described (Paulsson et al, 2019). Transcomplementation of the transposon mutant PW2884 was done by amplifying pba with 5 -ACTATTCGGATCCATTAAAGAGGAGAAATTACACATGAG CATCACGAGGAC-3 and 5 -AGTCATGACAAGCTTTCA TTCGCGCTTGATGAGGATTTCCA-3 , digested with BamHI and HindIII, and cloned into the complementation plasmid pUCP22Not.…”
Section: Dna Cloning and Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6 × His-tagged proteins were expressed in E. coli BL21(DE3) (Novagen) after induction with 1 mM IPTG. Expressed proteins were purified on Ni-NTA resin columns (GE Healthcare, Chicago, IL) as previously described (Paulsson et al, 2019). Transcomplementation of the transposon mutant PW2884 was done by amplifying pba with 5 -ACTATTCGGATCCATTAAAGAGGAGAAATTACACATGAG CATCACGAGGAC-3 and 5 -AGTCATGACAAGCTTTCA TTCGCGCTTGATGAGGATTTCCA-3 , digested with BamHI and HindIII, and cloned into the complementation plasmid pUCP22Not.…”
Section: Dna Cloning and Protein Expressionmentioning
confidence: 99%
“…The beads were incubated in PBS containing 1% milk and 0.05% Tween-20 (PMT) and transferred to 96-well V-bottom microtiter plates. His-tagged Pba or OprG as the control in PMT (Paulsson et al, 2019) was added to the beads and incubated for 1 h at 22 • C on a shaker (500 rpm). The beads were sedimented by gentle centrifugation (20 × g, 2 min), the excess liquid carefully removed, and then washed with PMT.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…In particular, we investigated dual stress conditions in Pseudomonas aeruginosa , which differs significantly from E. coli despite both being Gram-negative bacteria. P. aeruginosa inhabits very different niches in the human body, such as the airways and skin, compared to E. coli , which thrives in the gastrointestinal system [ 13 , 14 ]. Genetically, P. aeruginosa and E. coli can harbor significantly different-sized genomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among the pathogens that bind to host HS chains are parasites like Plasmodium falciparum [ 70 ]; bacteria, such as Escherichia coli [ 71 ], Pseudomonas aeruginosa [ 72 ], Borrelia burgdorferi [ 73 ] or Mycobacterium tuberculosis [ 74 ]; and many viruses, amongst which are found Human Papilloma virus, Herpes viruses and Human Immunodeficiency Virus-1 [ 75 , 76 ]. In addition, recently it was reported that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) entry in human cells is mediated through the binding to HS chains in a length and sequence-dependent manner [ 49 , 77 , 78 , 79 , 80 ].…”
Section: Heparan Sulfate Biological Activitiesmentioning
confidence: 99%